IMPROVING STUDENTS LEARNING OUTCOMES USING GROUP INVESTIGATION METHOD - Ivan Veriansyah; Ihsan Nurhakim; Pitalis Mawardi (GeoEco, 2025)
This research is Classroom Action Research which aims to improve student learning outcomes using the Group Investigation method. This research was carried out in 1 cycle consisting of four stages, namely planning, implementing actions, observing and reflecting. Because the expected results have been achieved, only 1 cycle is carried out without a second cycle. The results of the research show a significant increase in student learning outcomes in oceanography courses for semester 2 students in Geography study program at PGRI University of Pontianak. In pre-action it was found that there were still 89% of students who could not achieve the minimum score with an average score 44.2. After implementing the group investigation method in the class, it was found that  the student's score increased to 77 with the student completion rate reaching 82%. This shows that the group investigation method is very effective in improving student learning outcomes because this model guide students to get involve in internalizing and reshaping information actively. Beside that, students build understanding from within, not from external sources which encourages a better understanding of the topics.